Kartel Angkutan Kontainer Pelabuhan Belawan Tahun 2011 Dan 2012 - Dhiyan Utama (Lex Renaissance, 2020)
The rule of evidence in the existence of a price fixing agreement according to Article 5 of Law No. 5 of 1999 on Monopoly and Unfair Business Competition refers more to material evidence without prejudice to written evidence as formal evidence. Therefore, this study aims to analyze: first, what are the evidences that can be used by the Business Competition Supervision Commission (KPPU) in examining alleged cartel violations; and second, what is the rule of evidence which is carried out by KPPU in examining alleged cartel violations. This is a normative research with statutory approach and case studies. The results conclude that the actions of the business actors as reported parties tend to be the actions that are prohibited by law. Meanwhile, the KPPU Decision No. 06/KPPU-I/2013 on the Cartel Case of the Belawan Port Container Transport Tariff in Indonesia, in the process of proving it, applies indirect evidence as a guide to complete the evidence in the Commission Council session. The basis for the consideration of the District Court and Supreme Court is the belief that indirect evidence is not regulated in Indonesian procedural law. However, in its development, in 2011 the Supreme Court began to acknowledge indirect evidence through the Supreme Court Decision on rigging tender case No. 906K/Pdt.Sus/2010.